Electronic health record system (EHR) adoption:from Bangaladesh medical students’ perspective - Saquib, Nazmus; Mohamed Jalaldeen, Mohamed Razi (2015)
Paper base health care systems create number of problems. Considerable amount of data recording and storage cost with protection from fire, water etc., improper documentation, poor accessibility of medical record, fragile or lost document, ambiguous note of physician, and fragmentation of patient document cause ambiguity in health care system. To overcome, most of the countries have shown their keen interest to adapt electronic health record (EHR) systems. Bangladesh, as one of the most populated countries, undeniably will be benefited by such systems. However, very limited information is available in the literature about current and future medical doctors’ perception towards EHR in third world countries, such as Bangladesh. Therefore, the current study aims to investigate the level of behavioral intention and the influencing factors towards EHR adoption by collecting data from 238 medical students from two Bangladesh medical colleges. The finding shows that the respondents are moderately intent to use EHR and all three factors; performance expectancy, effort expectancy, and social influence that were considered to be influencing their intention were emerged as predictors.